The personal is political: articulating women's citizenship through three African feminist blogs - Carelse, Aimee (Centre for Film and Media Studies, 2017)
Mediated public spaces both on and offline privilege the educated male elite, and thus cannot address the specific needs of women (Huyer and Sikoska, 2003:2), or their points of view. This study aimed to explore the extent to which three African feminist blogs realise the democratising potential of the blogosphere as well as the ways in which they articulate the concerns and perspectives of women whose vantage points are often silenced by mainstream discourses of citizenship. As a specifically gendered platform within a feminist public sphere, these blogs offer insight into the fluidity of the private/public dichotomy in online media spaces, and how this determines particular discourses of citizenship both on and offline. Using a qualitative-quantitative content analysis of 45 blog posts across three African feminist blogs (Adventures from the Bedrooms of African Women, Her Zimbabwe, and MsAfropolitan) during July and August 2016, this study investigated how women's engagement with feminist issues is enabled by alternative online media spaces, and in what ways blogs offer African women a relatively democratic space for sharing and discussion. Through an analysis of blog content, the study revealed that contributors deploy particular communicative strategies such as first-person narration, reflection of personal experience in relation to broader social, economic and political issues, and a confessional intimacy that altogether prioritise women's voices and personal lived realities. The topics discussed in the content of blogs cut across public and private life, testifying to a need to move away from ideological conceptualisations of public engagement that delegitimise women's participation in the public sphere. It also makes a case for the reconsideration of the terms "public" and "politics" and what counts as both in a technologically dynamic society in which marginalised groups are continuing to explore alternative avenues for communication and self-expression.